Partisipasi Masyarakat Terhadap Bela Negara Dalam Rangka Ketahanan Nasional. - , Edy Permana Wahyu Siswanto; , Prof. Dr. Edhi Martono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis is talking about the public role in country assistance for increasing national tenacity. With the research purpose to know and analyze the society understanding of concerning countryâs nurture, as a commitment from society in the spirit of county nurture. Collecting data is distributed by questionnaire and interviewing about 100 respondents with the description analysis method to describe and measure accurately about particular social phenomenon and the matter role of society in Pasir Gunung Selatan, subdistrict Cimanggis, Depok. Understanding of society in Pasir Gunung Selatan, Depok that concerning values of countryâs nurture is high. Reflected by amourousness of society to their homeland, which is know and understand about the territory of indonesia, proud as a part of indonesian society, strong belief to Pancasila as state ideology, and patent the property about right, sense and work of state culture. The awareness of owning and state and country from Pasir Gunung Selatan Depok is well concerned. and reflected by the involvement directly in any social activities in order to create harmony, unity of the state. The role of society in Pasir Gunung Selatan, Depok is relatively small, mainly to arrange the plan to establish the civial defense unit (Hansip) or public opposition (Wanra). Where the society has never invited to comunnicate or discuss with related officials. But, the role of society indirectly is good enough and refleted by the involvement of society to develop and maintain public and social facility, life in harmony among the difference of, religion, ethnic, origin , or nation. The high willingness from the society to be the model for other societies is implemented through the prevention of gambling, and report every criminal action. Etc. Society commitment of Pasir Gunung Selatan, Depok in treating any problems, include their involvement in state nurture, among others , as citizen of Unity State of the Republic Of Indonesia. Ready to scarify energy, mind, property and life to defend state if needed, prioritize the togetherness and mutual help to develop, appreciate the difference of religion, ethnic, nation and race, is implemented in harmonius life behavior and attitude, keep secutity and orderliness of society, activate enviromental security system (siskamling) and eliminate any kind of gambling.